Integrin Activation - Woodside, D. G.; Liu, S.; Ginsberg, M. H. (Thrombosis and Haemostasis, 2001)
Integrins are cell surface adhesion receptors that participate in a variety of important processes throughout the vasculature. Here we summarize some recent findings on the regulation of integrin mediated cellular adhesion. Particular emphasis is placed on the regulation of integrin affinity for ligand (activation), although this is just one mechanism by which regulation of integrin-dependent cell adhesion can occur. Also discussed are recent observations on the structural basis of integrin activation, the role of the cytoplasmic domain in integrin affinity regulation, and potential mechanisms by which activation signals are propagated from integrin cytoplasmic domains to the extracellular ligand binding domain.
Keywords: Integrin; adhesion; affinity regulation; cytoplasmic domain; transmembrane domain